Impact of Macro-level Language Policies on Micro-level Language Practices and Ideologies of the Memons and Malays of Sri Lanka - Rassool, R. (University of Jaffna, 2025)
In Sri Lanka, there is little official acknowledgment of or discussion on the preservation of its lesser-known languages. Perhaps this is to be expected, in a country where the politics between the two major languages – Sinhala and Tamil – has led to interethnic violence that lasted over 30 years. There are only three languages mentioned in the Constitution – Sinhala and Tamil, the official and national languages, and English, which is termed the ‘link’ language. However, there are several other languages which are facing various threats to their survival. In this context, the present study investigates the manner in which Sri Lanka’s macro-level language and language-in education policies of the 1940-1950 period have impacted the language practices and ideologies of two of the communities of lesser-known languages: the Memons and Malays of Sri Lanka. Although the journeys that brought these communities to Ceylon are very different, they both practice the Islamic faith, and members of both communities believe that their languages are now endangered. This study employs a sequential research design where a quantitative study of the language practices and ideologies of 176 Memons was followed by semi-structured interviews with several participants from the Memon and Malay communities who were directly impacted by the language and language-in-education policy implemented during the 1940-50 period. The findings reveal that these macro-level changes resulted in the language repertoires of these participants increasing because they became proficient in Sinhala/Tamil, which was the medium of instruction in school. The way this change is viewed by the participants is reflective of their ideologies surrounding their own language – for some it meant a threat to the survival of their mother tongue and for others it meant a broadening of their linguistic repertoire, which was viewed as having a positive impact on their identity as Sri Lankans. The study concludes by drawing attention to the complex relationship between policies, identities, and ideologies in the contemporary Sri Lankan context.
Keywords: Language policies; Language practices; Memon; Malay; Ideologies